Upaya Hukum dalam Perundingan Binapartit - Ustien, Dewi Oktoviana (Universitas Batanghari Jambi, 2022)
The demands of industrialization are increasingly important for the progress of a country. Therefore, a set of laws is needed which can become a separate forum for dealing with disputes within companies, in this case through bipartite negotiations. Bipartite negotiations are the first attempt taken to resolve industrial relations problems that occur. Therefore, it is interesting to carry out an in-depth analysis regarding the importance of conducting bipartite negotiations in resolving industrial relations disputes which will form the legal basis for the agreement. Bipartite negotiations as an initial effort to resolve industrial relations disputes require good faith in the negotiation process, the formation of collective agreements, and the implementation of collective agreements. Accuracy and prudence are also needed in the formulation of collective agreements so that the agreement clauses do not result in losses or problems in its implementation. The results of this study indicate that the effectiveness of Bipartite LKS plays an active role as a media for positive deliberations to be used as a place for communication and consultation regarding new policies from the company as well as a place for expressing the aspirations of the working parties to achieve policies that do not harm either party. In addition, LKS Bipartite is also a preventive tool to create a harmonious, focused work environment that is in line with the company's vision and mission.